The Manipulation of Folate Biosynthesis in Lactic Acid Bacteria with a Folate Analog and Enhancers - Mahara, Fenny Amilia; Nuraida, Lilis; Nurjanah, Siti (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2024)
Folate biosynthesis in Lacticaseibacillus rhamnosus R23 isolate of breast milk and Limosilactobacillus fermentum JK13 isolate of kefir granules was manipulated by stressing them with a folate analog (methotrexate) to increase extracellular folate production. Extracellular folate production was further enhanced in isolate R23 (as a folate-efficient probiotic) by adding various enhancer compounds (PABA, glutamate, combination PABA-glutamate, CaCl2, and ascorbic acid) in a folate-free medium. Extracellular folate analysis was done using a microbiological assay that quantified all forms of folate in the samples. Both isolates could grow in folate-free medium containing methotrexate (2.5 mg/L); however, random mutant colonies of both had no increase in extracellular folate production. The resistance mechanism against methotrexate did not trigger excessive extracellular folate production but caused bacterial filamentation. Adding various enhancer compounds also did not significantly increase the extracellular folate production of isolate R23, probably due to the inadequate concentration of the compounds. This study's results indicate that stress exposure to methotrexate seems to be ineffective to increase the extracellular folate production of isolates R23 and JK13. The formation of bacterial filaments in response to stress exposure to methotrexate is possibly a new mechanism that has not been previously reported regarding the mechanism of methotrexate resistance by lactic acid bacteria. This study requires further investigation primarily evaluating intracellular folate concentrations and finding optimum concentrations of different folate biosynthesis enhancer compounds.